Renewable energy-based power generation in Antarctica: Roadmap for optimal sizing, placement and uncertainties prediction using AI-guided technological advances - Fahad Shinwari, Muhammad; Zahim Sujod, Muhamad; Mohd Saad, Norhafidzah; Mohamed Kamari, Nor Azwan; Zalani Daud, Muhamad; Arslan, Erhan (Ukrainian Antarctic Journal, 2025)
Antarctica, the most remote and environmentally extreme region on Earth, presents unique challenges for energy generation due to its harsh climate, isolation, and logistical constraints. The continent’s research stations, vital for advancing global understanding of climate change, glaciology, ecosystem, and environmental studies, have historically relied on fossil fuels for power, which poses significant logistical and environmental risks, high operational costs, and ethical concerns related to fossil fuel usage in such a pristine environment. This paper provides a comprehensive review of the current landscape of renewable energy adoption in Antarctica, focusing on key research stations such as Princess Elisabeth Station, McMurdo Station, and others that have adopted solar, wind, and hybrid power systems. The paper also discusses the major challenges to widespread renewable energy adoption, including extreme weather conditions, temperature fluctuations, equipment reliability issues, seasonal energy variability, and technological limitations in energy capture and storage systems capabilities. In response to these challenges, the paper explores the potential of advanced computational and artificial intelligence methods to enhance renewable energy system planning in Antarctica. Furthermore, it highlights emerging opportunities for improving renewable energy efficiency and reliability by integrating advanced technologies such as Grey Wolf Optimisation for optimal energy source placement, Random Forest Regression for weather prediction, and innovations in hybrid solar and wind power. The findings underscore the critical need for technological advancements and international collaboration with the Polar Research Institute, Türkiye, to improve energy sustainability, specifically in Horseshoe Island, as well as across the broader Antarctic region. The research concludes by offering recommendations for future research directions, including the implementation of robust data-driven forecasting models and high-performance energy storage technologies. These strategies aim to support the full transition of Antarctica’s energy infrastructure to renewable sources, in alignment with urgent global goals to reduce carbon emissions and the imperative to protect one of the Earth’s most fragile ecosystems.